2010
DOI: 10.1074/jbc.m110.187443
|View full text |Cite
|
Sign up to set email alerts
|

Brain-specific Phgdh Deletion Reveals a Pivotal Role for l-Serine Biosynthesis in Controlling the Level of d-Serine, an N-methyl-d-aspartate Receptor Co-agonist, in Adult Brain

Abstract: In mammalian brain, D-serine is synthesized from L-serine by serine racemase, and it functions as an obligatory coagonist at the glycine modulatory site of N-methyl-D-aspartate (NMDA)-selective glutamate receptors. Although diminution in D-serine level has been implicated in NMDA receptor hypofunction, which is thought to occur in schizophrenia, the source of the precursor L-serine and its role in D-serine metabolism in adult brain have yet to be determined. We investigated whether L-serine synthesized in brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 62 publications
4
94
0
Order By: Relevance
“…Correspondingly, neurotoxicity associated with ischemia elicited by middle cerebral artery occlusion is reduced in Srr knock-out mice (Mustafa et al, 2010). The depletion of D-serine associated with Phgdh deletion is similar in magnitude to that after Srr deletion (Basu et al, 2009;Yang et al, 2010). Therefore, PHGDH inhibitors might offer benefit in attenuating neurotoxicity in vascular stroke and other diseases involving neurotoxicity linked to NMDAR overactivation.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Correspondingly, neurotoxicity associated with ischemia elicited by middle cerebral artery occlusion is reduced in Srr knock-out mice (Mustafa et al, 2010). The depletion of D-serine associated with Phgdh deletion is similar in magnitude to that after Srr deletion (Basu et al, 2009;Yang et al, 2010). Therefore, PHGDH inhibitors might offer benefit in attenuating neurotoxicity in vascular stroke and other diseases involving neurotoxicity linked to NMDAR overactivation.…”
Section: Discussionmentioning
confidence: 74%
“…Mice containing targeted mutations of Srr and radial glia/astrocyte-specific deletion of Phgdh have been described previously (Basu et al, 2009;Yang et al, 2010). BAC transgenic animals [Tg(Srr-EGFP)KJ355Gsat/Mmucd] were obtained from the GENSAT/Mutant Mouse Regional Resource Center.…”
Section: Methodsmentioning
confidence: 99%
“…The biosynthesis pathway of D-serine starts from a glycolytic intermediate, 3-phosphoglycerate, in the central nervous system. After three-step reactions from the intermediate, L-serine is synthesized in astrocytes and then converted into D-serine by SRR (30). Both serine enantiomers are deeply related to neurophysiology; L-serine is a neurotrophic factor essential for brain morphogenesis (31,32), whereas D-serine is a prerequisite for glutamatergic neurotransmission mediated by synaptic NMDA receptors (13,18,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…In the first step of the phosphorylation pathway, 3-phosphoglycerate derived from glycolysis is metabolized into phosphohydroxypyruvate by PHGDH, a rate-limiting enzyme. Yoshida et al have successfully generated PHGDH-knockout mice and demonstrated that systemic PHGDH-knockout embryos die 13.5 d post coitum (18), whereas brain-specific PHGDHknockout mice are viable despite microcephaly (19). These results clearly showed that the serine provided from the mother did not satisfy their requirement and the fetus needs the de novo synthesis of most of the serine for tissue growth and development.…”
mentioning
confidence: 79%
“…Thus, sensitivity of the amino acids sensors may therefore have increased in the rats maintained on a 6% casein diet. It has been demonstrated that de novo synthesis of asparagine and serine was critical for cellular growth and function (16,(18)(19)(20)(21). ASNS and PHGDH are known to be expressed in several tissues at different levels.…”
Section: Discussionmentioning
confidence: 99%